What does state-subsidized outsourcing of domestic work do for women's employment? The Belgian service voucher scheme. (May 2018) - Raz-Yurovich, Liat; Marx, Ive
The European Commission, as well as national governments and national lobby groups, have actively promoted the extension of the domestic service sector since the 1990s in response to the prospect of structurally sluggish employment growth among the least skilled and the perceived need for more social investment. The Belgian service voucher scheme, the most heavily subsidized scheme of this type in the European context, yielded growing numbers of domestic service employees, users and employing companies since its enactment in January 2004. The purpose of this study is to identify whether this scheme was successful in increasing employment rates among low-skilled women in Belgium and to assess whether its employment effects have extended beyond this group of women and affected the employment rates of medium-skilled and highly skilled women. Using time-series analyses and difference-in-differences models for the period ranging from the first quarter of 1999 until the second quarter of 2014, our results demonstrate that the scheme had both short-term and long-term positive effects on employment rates of low-skilled women. However, a reversal in their employment rates during the economic recession is also found, which brought their employment rates to a nadir in 2008. We further found that the scheme's impact extended beyond the employments of low-skilled women to positively affect the employment rates of the highly skilled women.